2018
DOI: 10.1155/2018/6796839
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Human Coronavirus 229E Associated with Acute Respiratory Distress Syndrome in a Healthy Adult

Abstract: Human coronavirus 229E (HCoV-229E) is one of the first coronavirus strains being described. It is linked to common cold symptoms in healthy adults. Younger children and the elderly are considered vulnerable to developing lower respiratory tract infections (LRTIs). In particular, immunocompromised patients have been reported with severe and life-threatening LRTIs attributed to HCoV-229E. We report for the first time a case of LRTI and acute respiratory distress syndrome developed in a healthy adult with no como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 21 publications
0
51
0
6
Order By: Relevance
“…15 However, in instances of immunocompromise or underlying cardiopulmonary disease, they can cause pneumonia or bronchitis. 16 On the other spectrum, the SARS-CoV, MERS-CoV, and SARS-CoV-2 have been known to causing life-threatening respiratory failure. 17 CoVs have also been known to manifest in other regions apart from the respiratory tract, including the gastrointestinal tract and ocular tissues.…”
Section: Human Coronaviruses and The Evidence For Ocular Manifestationsmentioning
confidence: 99%
“…15 However, in instances of immunocompromise or underlying cardiopulmonary disease, they can cause pneumonia or bronchitis. 16 On the other spectrum, the SARS-CoV, MERS-CoV, and SARS-CoV-2 have been known to causing life-threatening respiratory failure. 17 CoVs have also been known to manifest in other regions apart from the respiratory tract, including the gastrointestinal tract and ocular tissues.…”
Section: Human Coronaviruses and The Evidence For Ocular Manifestationsmentioning
confidence: 99%
“…In children, severe respiratory tract CoV infections require hospitalization in about 10% of cases and have been associated with febrile seizure in those less than 1 year old ( Carman et al, 2018 ; Heimdal et al, 2019 ). CoV infection can also be severe in the elderly requiring hospitalization and can even cause acute respiratory distress syndrome (ARDS) ( Falsey et al, 2002 ; Vassilara et al, 2018 ). Zoonotic CoVs have a natural predilection for emergence into new host species giving rise to new diseases most recently exemplified in humans by severe acute respiratory syndrome coronavirus (SARS-CoV), and Middle East respiratory syndrome coronavirus (MERS-CoV) ( de Wit et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, severe consequences such as pneumonia and acute respiratory distress syndrome have been described in some cases. [2][3][4] Gaunt et al has found the lack of association between HCoV-229E and significant respiratory symptoms in healthy individuals. This may be in part due to infrequent respiratory viral testing in the adult population.…”
Section: Discussionmentioning
confidence: 99%